Musa Information Resources: Biodiversity, Disease and Pest Management Database - Arora, Vasu; Kapoor, Neera; Fatma, Samar; Jaiswal, Sarika; Iquebal, MirAsif; Rai, Anil; Kumar, Dinesh (Asian Journal of Biological and Life Sciences, 2017)
Genus Musa is of great importance worldwide due to the commercial and nutritional value of cultivated varieties belonging to the family Musaceae of order Zingiberales that includes bananas and plantains which are monocotyledonous, herbaceous flowering plants. Banana has valuable nutritional content of vitamin C, B6, minerals and dietary fibre and is considered to be rich energy source. We have designed a comprehensive web-based database, Musa Information Resources to provide comprehensive information available world-wide at a single platform. The database provides access to the morpho-taxonomic data, geographical location, economic status and usage of the various Musa varieties, passport data for 3630 accessions of banana available worldwide. Varieties can be classified based on the morphological features. The database also provides disease and pest management information, in order to protect the crop from harmful infections. The sophisticated web-based graphical user interface allows efficient and desired retrieval of data, making it a comprehensive and intricate tool. Musa Information Resources can be accessed at http://webtom.cabgrid.res.in/Musa_resources/
Keywords: Nil